Genocias ir rezistencija Nr. 2(2) - Vovk, Oleksandr; Anušauskas, Arvydas; Starkauskas, Juozas; Streikus, Arūnas; Kuodytė, Dalia; Kokurinas, Aleksandras; Noormets, Tiit; Gurjanovas, Aleksandras; Strods, Heinrihs; Roman, Wanda Krystyna; Jansons , Ritvars; Vasilevskis, Janis; et al. (Genocidas ir rezistencija, 1997)
Pilnas leidinys (nuskenuota popierinė versija)